Versatility of the BID Domain: Conserved Function as Type-IV-Secretion-Signal and Secondarily Evolved Effector Functions Within Bartonella-Infected Host Cells - Wagner, Alexander; Tittes, Colin; Dehio, Christoph (Frontiers in Microbiology, 2019)
Bartonella spp. are facultative intracellular pathogens that infect a wide range of mammalian hosts including humans. In order to subvert cellular functions and the innate immune response of their hosts, these pathogens utilize a VirB/VirD4 type-IV-secretion (T4S) system to translocate Bartonella effector proteins (Beps) into host cells. Crucial for this process is the Bep intracellular delivery (BID) domain that together with a C-terminal stretch of positively charged residues constitutes a bipartite T4S signal. This function in T4S is evolutionary conserved with BID domains present in bacterial toxins and relaxases. Strikingly, some BID domains of Beps have evolved secondary functions to modulate host cell and innate immune pathways in favor of Bartonella infection. For instance, BID domains mediate F-actin-dependent bacterial internalization, inhibition of apoptosis or modulate cell migration. Recently, crystal structures of three BID domains from different Beps have been solved revealing a conserved fold formed by a four helical bundle topped with a hook. While the conserved BID domain fold might preserve its genuine role in T4S, the highly variable surfaces characteristic for BID domains may facilitate secondary functions. In this review, we summarize our current knowledge on evolutionary and structural traits as well as functional aspects of the BID domain with regard to T4S and pathogenesis.